2015
DOI: 10.5039/agraria.v10i1a4708
|View full text |Cite
|
Sign up to set email alerts
|

Brassinosteroide e fungo micorrízico arbuscular na produção do porta-enxerto tangerineira ‘Cleópatra’

Abstract: RESUMOTanto o brassinosteroide quanto a inoculação com fungos micorrízicos arbusculares (FMA) favorecem o crescimento e a absorção de nutrientes pelas plantas. Entretanto, não há relatos de experimentos testando a combinação desses insumos em mudas de Citrus reshni (tangerineira 'Cleópatra'). Assim, o objetivo deste trabalho foi avaliar o efeito da aplicação desses dois insumos sobre o crescimento e o estado nutricional de mudas de tangerineira 'Cleópatra', na fase final do enviveiramento. O experimento foi co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…'Cleopatra' mandarin seedlings inoculated with A. scrobiculata provided increases of 11.9 % and 15.6 % in the Fe and Mn contents, when compared to the control treatment (Freitas et al 2015). Divergent results were reported for inoculation with Rhizophagus clarus, which reduced the Cu contents in 'Paulsen 103' grapevine plants (Rosa et al 2016).…”
Section: Amf Isolatesmentioning
confidence: 94%
“…'Cleopatra' mandarin seedlings inoculated with A. scrobiculata provided increases of 11.9 % and 15.6 % in the Fe and Mn contents, when compared to the control treatment (Freitas et al 2015). Divergent results were reported for inoculation with Rhizophagus clarus, which reduced the Cu contents in 'Paulsen 103' grapevine plants (Rosa et al 2016).…”
Section: Amf Isolatesmentioning
confidence: 94%
“…These results are in agreement with those reported by Freitas et al (2012), who verified that brassinosteroid doses exhibited a significant effect on nitrogen content, with an increasing linear behavior, with 1.0 mg L -1 providing an 11.1% increase in the nutritional content of pineapple plantlets when compared to the controls. Freitas et al (2015), when working with 'Cleopatra' mandarin plantlets, reported that 1.0 mg L -1 brassinosteroids associated with arbuscular mycorrhizal fungi led to a 15.4% increase in the aerial dry mass nitrogen content. Diniz et al (1999) evaluated in vitro macronutrient absorption by banana explants, and reported that nitrogen content was higher during the first 10 days, decreasing as a function of culture time.…”
Section: Variation Causes F Valuesmentioning
confidence: 99%
“…Brassinosteroids are a class of plant steroid hormones that act on cell elongation, allowing the growth of plants (Baghel et al, 2019). However, its effect depends on the growth stage of the plant (Freitas et al, 2015), the applied concentration (Freitas et al, 2014;Wei and Li, 2016) and the presence or absence of environmental stress (Tanveer et al, 2019). It is efficient in increasing resistance, especially at high temperatures, drought and salinity (Vardhini, 2012).…”
Section: Introductionmentioning
confidence: 99%